(untitled) (Journal of the College of Basic Education, 2024)
The aim of the research is to prepare educational units according to the effect of the Bokartz model on some physical abilities and learning futsal skills for fifth-grade middle school students, and to identify the effect of the Bokartz model on some physical abilities and learning futsal skills for fifth-grade middle school students, and to identify the advantage of Two research groups (control and experimental) on some physical abilities and learning futsal skills for fifth grade middle school students. The two-group experimental research approach involves dividing participants into two groups, one known as the experimental group that is exposed to the independent influence, and the other known as the control group that is not exposed to this influence. This approach aims to measure the effect of the independent variable on the dependent variable by comparing the results between the two groups. The researcher intended to establish homogeneity and equality for the two research groups, and the research sample was selected non-significantly from them by the regular non-significant method (lottery). They are Division (A) to be experimental and Division ( C) Control) and each group consists of (16) students, constituting 29%, and this percentage is representative of the community. As for the students of Section (B), 10 students were chosen from them as an exploratory group and they were divided without any significance into two groups, an experimental group and a control group. The researcher used scientific questionnaires to identify physical abilities and their tests, in addition to futsal tests, and adopted methodological futsal skills within the middle school guide. After that, he proceeded to conduct a pre-test for the variables under research, and after that, an experiment was conducted that included the educational units, which the researcher prepared, amounting to 20 educational units according to The Bouckarts model using exercises with assistive devices from before him, and the time of the educational unit was (45) minutes, at a rate of two units per week. After that, the researcher conducted the post-test, and the statistical bag and some statistical laws were adopted to extract the results that led the researcher to conclusions, the most important of which is employing the Bouckarts model with exercises with assistive devices, if the model works to an increase. Students’ competencies within the lesson through its three stages in terms of their physical abilities and learning futsal skills. The Bokarts model contributes to preparing students who have the ability to be autonomous in learning, especially in the middle school stage, and it has great contributions to improving the quality of learning. The learner was given a role in modifying his strategies based on his evaluation of his performance. This increases the importance of self-evaluation in the Boeckarts model due to the possibility of improvement and modification of performance. One of the most important recommendations is to emphasize the application of the Boeckarts model in teaching indoor football to enhance physical abilities and develop students’ skills during the three stages to enhance the effectiveness of the lesson.